Cellulose nanofibrils/polyvinyl acetate nanocomposite adhesives with improved mechanical properties. (20th January 2017) - Chaabouni, Ons; Boufi, Sami
Highlights: Nanocomposite adhesive based on Cellulose nanofibrils and PVA latex was prepared. The adhesive was prepared by a simple mixing approach. Addition of CNFs strongly enhanced the shear strength both at wet and dry conditions. The addition of CNFs reduced the water sensitivity of PVA adhesive. Abstract: Cellulose nanofibrils (CNFs) are nanoscale cellulose produced from renewable resources with strong reinforcing potential when included in a polymer matrix. In this work, the effect of the addition of CNFs on the properties of waterborne polyvinylacetate (PVA) adhesive was investigated. Adhesive formulations with different contents in CNFs from 1 to 10 wt.% was prepared by simple mixing of PVA dispersion with CNFs suspension in water. The viscosity of the adhesive increased with the addition of CNFs, namely over a content of 5%. Shear strength of wood joints at dry as well as wet conditions was improved by CNFs inclusion. Adding 10% of CNF to the PVA adhesive increased the shear strength by about 2 folds compared to the neat adhesive. This strengthening effect was explained by the strong reinforcing impact brought by CNFs inclusion in the PVA matrix. The addition of CNFs also improved the water resistance of PVA adhesive and strongly enhanced the mechanical performance in wet conditions, namely over 7% of CNF content.